2011
DOI: 10.1111/j.1440-1843.2011.01973.x
|View full text |Cite
|
Sign up to set email alerts
|

Pleural controversy: Closed needle pleural biopsy or thoracoscopy—Which first?

Abstract: The most efficient and cost-effective approach to the diagnosis of pleural exudates remains controversial. Important considerations include the respective diagnostic yields of thoracocentesis, closed pleural biopsy and thoracoscopy; the incremental gain in diagnostic yield when sequentially combining these investigations; and the role of various image modalities. The diagnostic yield of thoracocentesis is in the order of 60% for malignancy and >90% for tuberculosis. A second aspiration may increase the yield f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
97
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 80 publications
(99 citation statements)
references
References 58 publications
1
97
0
1
Order By: Relevance
“…The Abrams needle is indicated in pleural effusion without pleural thickening or nodularity. 4 Metintas et al found no significant differences in the sensitivities of medical thoracoscopy and CT-guided Abrams pleural needle biopsy in subjects with malignant pleural effusion. 6 The diagnostic sensitivities were 94% and 87%, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The Abrams needle is indicated in pleural effusion without pleural thickening or nodularity. 4 Metintas et al found no significant differences in the sensitivities of medical thoracoscopy and CT-guided Abrams pleural needle biopsy in subjects with malignant pleural effusion. 6 The diagnostic sensitivities were 94% and 87%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…1,2,[16][17][18] The optimal method for obtaining pleural tissue and a diagnosis in subjects with exudative pleural effusion of unknown etiology is controversial. 4 An important benefit of thoracoscopy is the ability to obtain a diagnosis, drain the effusion, and perform a pleurodesis during the same procedure. 17 However, thoracoscopy is more expensive and time consuming than other procedures.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations